TINGKAT PENDAPATAN KELUARGA, POLA ASUH ORANG TUA STIMULASI PERKEMBANGAN DAN PERKEMBANGAN BALITA - Nurul Khairani; Sanisahhuri Sanisahhuri; Fauziah Prasisti Yinisah (Universitas Pahlawan, 2020)
An important period in child development is toddlerhood. During this time, development of language skills, creativity, social awareness and others run very fast times and determines the next development and quality of human resources. The purpose of this research was to study the relationship between family income levels, parenting and developmental stimulation with development of toddlers aged 4-5 years in Dwi Wardani Kindergarten Bengkulu City. Type of this research was Survey Analytic with Cross Sectional design. Population of this study was all mothers with toddlers aged 4-5 years in Dwi Wardani Kindergarten Bengkulu City, as many as 32 mothers. Sample were taken using a Total Sampling amount of 32 mothers. Analysis were performed with univariate and bivariate analysis with the Chi-Square test (ï£2). The results of the study revealed that of the 32 mothers there were 17 mothers (53.1%) with low income levels, 24 mothers (75.0) who had democratic parenting, 16 mothers (50.0%) who had often carry out developmental stimulation, 25 mother (78.1%) who had toddlers with good development. There was not significant relationship between level of family income and development of toddlers, there was a relationship between parenting and development of toddlers with a category of close relationship, and there was a relationship between developmental stimulation and development of toddlers with a category of moderate relationship. Keywords: development of toddlers, developmental stimulation, family income level, parenting